Consumer choice and revealed bounded rationality - Paola Manzini; Marco Mariotti (Queen Mary University of London, Department of Economics, 2006)
We study two boundedly rational procedures in consumer behavior. We show that these procedures can be detected by conditions on observable demand data of the same type as standard revealed preference axioms. This provides the basis for a non-parametric analysis of boundedly rational consumer behavior mirroring the classical one for utility maximization.
Keywords: D1; D11; 330; Bounded rationality; Revealed preference; Consumer choice; Konsumentenverhalten; Beschr\~AƒÂnkte Rationalit\~AƒÂt; Offenbarte Pr\~AƒÂferenzen; Theorie